Políticas publicas del GAD municipal del cantón Santa Rosa para la disminución del comercio informal, año 2023 - Benalcazar Castillo, Fabian Andrey; Bravo Contreras, Andres Fernando (Machala, 2024)
This research in relation to public policies and informal trade shows that in the context of study in this case Santa Rosa there is a high rate of informal traders who do not act outside the legal regulations, this population finds in this activity a livelihood alternative, on the other hand, the Municipal Government has not formulated public policies to reduce this existing problem. In this sense, the general objective is to identify the public policies applied by the Municipal Government of the Santa Rosa canton to reduce informal commerce. The sociological theory on which the research was based is the structural functionalist theory because it sought to analyze, describe and explain the forms of organization that informal traders adopt in the development of the activities of exchange of goods and services, in addition to having a state of the art to address the variables to be investigated. The research methodology is considered an empirical-deductive approach, the type of research is basic, so it allows obtaining theoretical information from scientific articles, journals and books of the last 5 years to support with veracity the degree work, the methods applied are deductive and analytical-synthetic, likewise, to collect empirical information from the experiences the interview technique was applied; The following techniques were used to collect empirical information about the experiences: interviews with the Municipal Commissioner, Canton Councilman and Head of Urban Planning; an observation guide to learn about the physical aspects and a survey of informal merchants to obtain quantifiable data. The results obtained show that the socioeconomic factors are, according to those surveyed, the high costs of starting formal commerce (41.08%), as well as access to credit to start formal businesses (34.88%), on the other hand, 92.24% indicate that informal commerce does affect the socioeconomic development of Santa Rosa. On the other hand, 92.24% indicated that informal commerce does affect the socioeconomic development of Santa Rosa, in the same way in relation to urban development, 31% mentioned the obstruction of public roads, another important aspect is the strategies implemented by the Municipal Government, 44.18% indicated that they have meetings with merchants and regularization with merchants, in addition to 28.98% that affirmed the municipal ordinances. Given the information obtained, the Training Program for informal merchants in Santa Rosa has been proposed to promote formal commercial activity and improve their socioeconomic conditions. It is aimed at training informal merchants in Santa Rosa to formalize their commercial activity, with The purpose is to reduce, as well as insert those merchants into formality to achieve economic development and better standards of living for people, as well as income that contributes to satisfying needs and desires. In the same way, the intervention proposal provides an answer to the problems found in the diagnosis, as well as a chronogram of activities to be executed, through an operational plan and a respective budget and financing, in addition to a feasibility and viability analysis to meet the proposed objectives and achieve the expected results.
La presente investigación en relación a las políticas públicas y el comercio informal demuestran que en el contexto de estudio en este caso Santa Rosa existe un elevado índice de comerciantes informales que no actúan al margen de la normativa legal, esta población encuentra en esta actividad una alternativa de subsistencia, por otro lado, el GAD Municipal no ha formulado políticas públicas para reducir esta problemática existente. En tal sentido, se ha planteado el objetivo general es Identificar las políticas públicas aplicadas por el GAD Municipal del cantón Santa Rosa para la disminución del comercio informal. La teoría sociológica que se fundamentó la investigación es la estructural funcionalista debido a que se buscó analizar, describir y explicar las formas de organización que los comerciantes informales adoptan en el desarrollo de las actividades de intercambio de bienes y servicios, además de contar con un estado del arte para abordar las variables a investigar. La metodología de la investigación se considera un enfoque empírico-deductivo, el tipo de investigación es básica, por lo que permite obtener información teórica de artículos científicos, revistas y libros de los últimos 5 años para sostener con veracidad el trabajo de titulación, los métodos aplicados son deductivo y analítico- sintético, así mismo, para recopilar información empírica de las vivencias se aplicó la técnica de entrevista; dirigidas al comisario Municipal, Concejal del cantón y Jefe de Planeación Urbana; guía de observación para conocer los aspectos físicos y encuesta; dirigida a los comerciantes informales para obtener datos cuantificables. Los resultados obtenidos detallan que los factores socioeconómicos son según los encuestados los altos costos para iniciar el comercio formal indican el 38.12%, así como el acceso a créditos para emprender en negocios formales con 32.37%, por otro lado, el 92.24% indica que el comercio informal si afecta al desarrollo socioeconómico de Santa Rosa, de la misma forma en relación al desarrollo urbano el 28.16% menciona la obstrucción a la vía pública, otro aspectos importante son las estrategias implementadas por el GAD Municipal manifiestan que el 35.84% señala reunión con comerciantes y regularización con los comerciantes, además del 23.02% que afirman las ordenanzas municipales. Dada la información obtenida se ha planteado la Programa de capacitación a comerciantes informales de Santa Rosa que promueva la actividad comercial formal y mejore sus condiciones socioeconómicas., se encuentra direccionada a la capacitación de los comerciantes informales de Santa Rosa para formalizar su actividad comercial, con la finalidad reducir, así como también insertar a la formalidad a aquellos comerciantes para lograr un desarrollo económico y mejores niveles de vida en las personas, además de ingresos que contribuyan a satisfacer las necesidades y deseos. De la misma forma la propuesta de intervención brinda una respuesta al requerimiento de los problemas encontrados en el diagnóstico, así mismo cuenta con un cronograma de actividades a ejecutar, a través de un plan operativo y un respectivo presupuesto y financiamiento, además de un análisis de viabilidad y factibilidad para cumplir con los objetivos propuestos y alcanzar los resultados esperados.
Keywords: COMERCIO INFORMAL; POLITICAS PUBLICAS; FACTORES SOCIOECONOMICOS